Compound Control of Electromagnetic Linear Actuator Based on Fuzzy Switching - Zhu Jianhui; Wang Cheng; Dai Jianguo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Due to the motion control system of electromagnetic linear actuator (EMLA) is a nonlinear system with poor controllability, single control strategy has been difficult to meet the requirements of its control. A compound control strategy based on inverse system control (ISC) and proportional-integral (PI) is designed in this paper. Switching between two algorithms, which is based on the fuzzy rules, prevents the control algorithm to jitter and jump. System model is build under Matlab/Simulink to do simulation analysis. The designed controller is integrated into the system simulation model and the system software of digital signal processor (DSP) controller. Simulation and test results show that the compound control strategy using fuzzy switching rules achieves the smooth transition of two control algorithms, and the goal of any position location, and continuous adjustment in 0~4mm lift. Positioning accuracy is up to ± 0.02mm, while the response time is less than 10ms.